Competitiveness Through Consumer Loyalty: The Influence of Switching Costs - Marija Martinović (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Competitiveness depends on the relationship that a company has with its consumers. Consumer loyalty makes many benefits for companies like lower price elasticity, lower relationship costs, the possibility of increasing income over time, chance of achievement new customers because of loyal consumers' suggestions, lower sale and promotion efforts etc. The aim of the paper is to determine the effect of consumers' perception of quality, satisfaction and corporate image on developing consumer loyalty in bank sector. Another aim is to investigate the influence of switching costs on the relationship between the key loyalty predictors and the consumer loyalty comparing internet and traditional users. For that purpose, the research is conducted among the consumers of the top five banks in Croatia. The results indicate that switching costs moderate relationship between quality, satisfaction and corporate image more for internet users of bank services.
Keywords: 650; Competitiveness; Consumer loyalty; Bank sector; Switching costs